2005
DOI: 10.17221/5635-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Peat as a feed supplement for animals: a literature review

Abstract: ABSTRACT:Peat is an easily available natural material and a source of biologically active substances widely used, not only in agriculture but in human and animal medicine as well. In recent years, interest in the use of peat as a feed supplement has increased, particularly due to its capability to prevent enteric diseases and to stimulate growth in piglets and pigs. The purpose of this review was to compare the advantages and risks associated with the use of peat for animal nutrition based on the literature av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 39 publications
0
48
0
1
Order By: Relevance
“…As mycobacterial contamination of peat is quite common , its use as a feed supplement for piglets, without previous efficient disinfection targeted at devitalisation of mycobacteria, is highly risky due to the occurrence of tuberculous lesions in the lymph nodes . Its use may only be recommended in specified cases of recurrent health disorders in piglets, particularly those affected by diarrhoea (Trckova et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mycobacterial contamination of peat is quite common , its use as a feed supplement for piglets, without previous efficient disinfection targeted at devitalisation of mycobacteria, is highly risky due to the occurrence of tuberculous lesions in the lymph nodes . Its use may only be recommended in specified cases of recurrent health disorders in piglets, particularly those affected by diarrhoea (Trckova et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The potential risk of peat feeding is represented by its primary or secondary contamination with mycobacteria (Horvathova et al, 1997;Pavlik et al, 1999;Kazda, 2000;Matlova et al, 2003Matlova et al, , 2005Trckova et al, 2005). Despite the fact that Czech Republic has been declared to be a bovine tuberculosis-free EU state in 2004 (Anonymous, 2004a;Pavlik et al, 2005;Pavlik, 2006), tuberculous lesions in lymph nodes are consistently found in slaughtered pigs .…”
mentioning
confidence: 99%
“…[1] The literature refers to a wide spectrum of beneficial effects of peat and various peat preparations on organisms: stimulating effects on digestion, growth, and the immune system of the animals [2].…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of detectable living mycobacteria are inversely proportional to the depth from which the sample is taken, and viable mycobacterial cells were not found in the profile of peat from 70 cm and deeper (Kazda 2000;Trckova et al 2005Trckova et al , 2006a.…”
mentioning
confidence: 97%
“…The high content of fibre, meanwhile, increases the overall uptake of food, thus improving the weight gaining process in piglets. Also, the low pH of peat has bactericidal effects on pathogenic bacteria in the intestinal tract of piglets helping to prevent or decrease the intensity of diarrhoea (Roost et al 1990;Mesrogli et al 1991;Fuchs et al 1995;Trckova et al 2005).…”
mentioning
confidence: 99%